2010
DOI: 10.1309/ajcpjh6keusecqlu
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Extraoral Plasmablastic Lymphoma

Abstract: Plasmablastic lymphoma (PBL), initially characterized as an aggressive lymphoma arising in the jaw and oral mucosa in HIV-infected patients, was recently reported to occur with extraoral manifestations, heterogeneous histologic findings, and variable association with immunodeficiency states. We reviewed clinical, morphologic, and immunophenotypic features of 13 cases of PBL to determine whether these different subtypes represent distinct morphologic and clinical entities. Two distinct subtypes of PBL were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…There are a few reports in the medical literature of cases of extra-oral compromise as we could see in our patient. The immunophenotype of this lymphoid neoplasm is consistent with the plasma cell-markers associated antigens VSC38c and CD 138 AS CD28 ABD CD 45 [15] .…”
Section: Introductionsupporting
confidence: 61%
“…There are a few reports in the medical literature of cases of extra-oral compromise as we could see in our patient. The immunophenotype of this lymphoid neoplasm is consistent with the plasma cell-markers associated antigens VSC38c and CD 138 AS CD28 ABD CD 45 [15] .…”
Section: Introductionsupporting
confidence: 61%
“…The prognosis is usually very poor and reported survival is less than a year. Hansara et al reported a better overall survival in patients with PBL of extra-oral sites when compared to patients with oral PBL [10] . Some authors have described a better prognosis in HIV positive patients with PBL as compared to HIV negative patients with PBL [14] .…”
Section: Discussionmentioning
confidence: 98%
“…Some authors have reported that plasmacytic differentiation is more likely to be seen in extra-oral type of PBL [9,10] . On the other hand, others have reported plasmacytic differentiation in large percentage (57%) of oral PBL [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The landmark paper written by Delecluse et al [5], which gave the first description of PL, found HIV positivity in 15 of the 16 cases studied. However, it is also known that the there is a weaker association of EoPL with HIV [11]. Amongst the PL studies that examined for EBV, nearly 64% found EBV positivity.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%